A handmade influenza A virus teaching model for enhancing virology education - Li, Jincheng; Zhang, Leiliang (Frontiers in Education, 2025)
Influenza pandemics occur annually, highlighting the importance of understanding the influenza A virus (IAV) in the context of orthomyxoviruses and virology as a whole. However, many undergraduate students find the complex knowledge surrounding virology challenging to grasp., particularly the three-dimensional structure and dynamic processes of IAV. To address this issue, we developed a tangible, interactive, and cost-effective model using ultra-lightweight paper clay. This model visualizes the three-dimensional structure of IAV, its life cycle, antigenic variation, and the mechanisms underlying vaccines and antiviral drugs. Key features include a magnet-enhanced design that replicates molecular interactions, a reflective inner wall simulating viral infection dynamics, and reversible components illustrating processes such as replication and antigenic transitions. By engaging multiple senses, this hands-on model enhances comprehension, facilitates memory retention, and provides an accessible learning experience. Through improved virology literacy, students can better understand IAV and even disseminate accurate information to the general public. This model has received positive student feedback, demonstrating its potential for integration into virology curricula.